Criminal Liability Against Perpetrators of HOAX Spread in Indonesia - Rosyadi, Imron (Nursyam Centre, 2023)
The purpose of this article is to explain and examine the responsibility of perpetrators in the criminal act of disseminating information in the form of misleading fake news, especially based on Law Number 11 of 2008, let alone the blurring of norms related to the phrase fake and misleading news. One of the main problems of crime that occurs in society is the use of social media so the government needs to support the development of information technology through legal infrastructure and regulation so that the use of information technology must be carried out safely to prevent its misuse by taking into account the religious and socio-cultural values of the Indonesian people. This article is in the form of normative juridical research that is useful for finding solutions to legal issues that are the focus of study. The results showed that the perpetrators of spreading false news apply the principle